A Uniqueness Theorem for Stationary Kaluza-Klein Black Holes - Hollands, Stefan; Yazadjiev, Stoytcho (Communications in mathematical physics, 2011)
We prove a uniqueness theorem for stationary D -dimensional Kaluza-Klein black holes with D − 2 Killing fields, generating the symmetry group . It is shown that the topology and metric of such black holes is uniquely determined by the angular momenta and certain other invariants consisting of a number of real moduli, as well as integer vectors subject to certain constraints.